The Influence of Discipline and Job Satisfaction on the Performance of Teachers at SD Negeri 1 Bumi Kencana Central Lampung - Marsiska, Lusi; Ahmaludin, Ahmaludin (Ensiklopedia: Jurnal Pendidikan dan Inovasi Pembelajaran Saburai, 2024)
Discipline, as adherence to rules, and job satisfaction, reflected in positive feelings toward work, were considered crucial for creating a conducive educational environment. However, issues such as tardiness and limited facilities remained challenges. This study aimed to investigate the influence of discipline and job satisfaction on the performance of teachers at SD Negeri 1 Bumi Kencana, Central Lampung. The research was conducted at SD Negeri 1 Bumi Kencana due to its accessibility, data availability, and the relevance of observed issues. A descriptive quantitative method was used with a sample of 15 teachers. The independent variables were Discipline (X1) and Job Satisfaction (X2), while the dependent variable was Teacher Performance (Y). Data were collected through questionnaires and analyzed statistically. The results showed that Discipline (X1) had a significant effect of 61.1 persen on Teacher Performance (Y), while Job Satisfaction (X2) contributed 53.9 persen. When analyzed simultaneously, both Discipline and Job Satisfaction influenced Teacher Performance by 54.9 persen, with the remaining 45.1 persen attributed to other unexamined factors. These findings highlighted the importance of improving teacher discipline and job satisfaction as strategic efforts to enhance educational quality.